Combined domestic demand response and energy hub optimisation with renewable generation uncertainty. (December 2017) - Huo, Da; Gu, Chenghong; Yang, Gang; Blond, Simon Le
Abstract: The optimisation of energy hub modelling at domestic level exploits the redundancy of multiple energy carriers against customers' stochastic demand profiles, and thus increases system flexibility. On the other hand, demand response enables the shifting of deferrable appliances in response to energy carrier price to minimize the system cost and maintain customers' comfortability. Combining demand response schemes with energy hub approach yields further energy cost saving. However, the optimal operation of energy hub system may be affected by stochastic elements. In this paper, the uncertainty of solar radiation is modelled by 2 point estimated method and applied to an energy hub with demand response optimisation. The results demonstrate that incorporating demand response to energy hub optimisation brings 4% of additional energy cost saving for a single energy hub system, and that greater savings can be foreseen for large scale system.